SOCIOECONOMIC DETERMINANTS OF CONTRACEPTION AMONG MARRIED WOMEN IN SUB-SAHARAN AFRICA - Sogo Olaosebikan, Johnson; Adebayo Sunmola, Kazeem; Abayomi Atoyebi, Timothy; Dorcas Olodude, Opeyemi; Elizabeth Olaosebikan, Olayinka (African Journal of Social and Behavioural Sciences, 2024)
Low contraceptive uptake in the face of high fertility norms in sub-Saharan Africa has continued to create developmental challenges in the region. This study examined the literature on socioeconomic determinants of contraception among married women in sub- Sahara Africa. Desk review of thirty-three (33) relevant literature extracted through Google Scholar and key words such as socioeconomic, determinants, contraception, married women, aged 15-49 and sub-Saharan Africa was employed after filtering irrelevant articles to achieve the objective of the study. The study showed that the fertility rate is still high in the region because of the low contraceptive prevalence rate. The high fertility and low contraceptive rate will lead to population explosion and further deepen the poverty level of the region. The study further showed a gradual improvement in the prevalence of contraceptives and the adoption of long-acting reversible and nonreversible methods such as Intra-uterine devices, implants and sterilization. This will substantially reduce fertility rate and hence pave way for economic growth and development in the area. Moreover, the study showed that urban-rural gap in contraceptive use still subsists in the region except in situations where there are intervention programs such as counselling of married women, distribution of family planning products for free, payment of allowances to women who are able to reduce the number of children they bear and counselling of breastfeeding women on reproductive issues. The major factors that determine contraceptive uptake are education, residence, cultural influence such as desire for children and son preference, misconception and erroneous beliefs about contraception. The study recommends that the governments make education free and compulsory at both primary and secondary schools especially for women. Family planning counselling should be offered to women especially in rural areas to bridge urban-rural gap in family planning uptake. Governments in the region should educate the masses on the danger of having too many children as well as the benefits of family planning programs. Programme interventions that target married women such as tax relief and allowances to those who have fewer children should be implemented to encourage contraceptive uptake in the region. In addition, policies aim at encouraging the use of long-acting reversible and nonreversible methods such as implants, intra-uterine device and sterilization should be implemented to